2020
DOI: 10.1101/2020.07.05.154906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symbiont-mediated fly survival is independent of defensive symbiont genotype in the Drosophila melanogaster-Spiroplasma-wasp interaction

Abstract: AbstractWhen a parasite attacks an insect, the outcome is commonly modulated by the presence of defensive heritable symbionts residing within the insect host. Previous studies noted markedly different strengths of Spiroplasma-mediated fly survival following attack by the same strain of wasp. One difference between the two studies was the strain of Spiroplasma used. We therefore performed a common garden laboratory experiment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thus, the higher RIP2 copy numbers detected in MSRO-Br could reflect a higher number of chromosomal copies, or a higher abundance of extrachromosomal copies, which could be condition-dependent. If RIP2 gene copy numbers differ between MSRO-Br and MSRO-Ug, they could be related to the higher degree of overall protection against certain wasps reported for MSRO-Br (Jones and Hurst 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the higher RIP2 copy numbers detected in MSRO-Br could reflect a higher number of chromosomal copies, or a higher abundance of extrachromosomal copies, which could be condition-dependent. If RIP2 gene copy numbers differ between MSRO-Br and MSRO-Ug, they could be related to the higher degree of overall protection against certain wasps reported for MSRO-Br (Jones and Hurst 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental over-expression of these, and the Group 2 “restored” genes, in the absence of Spiroplasma , could be used to test whether they influence the outcome of parasitism by L. heterotoma and other wasps, including those against which s Mel confers stronger rescue (e.g. L. boulardi or L. victoriae ; Mateos et al, 2016; Paredes et al, 2016; Jones and Hurst, 2020a)…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we used an RNA-seq approach to evaluate the transcriptomic response of D. melanogaster during interactions involving Spiroplasma and two wasps that are generalists of the genus Drosophila : the Spiroplasma -susceptible L. heterotoma ; and the Spiroplasma -resistant Ganaspis hookeri . In addition, we evaluated the effect of wasp parasitism on the expression of Spiroplasma RIP genes in two closely related substrains of s Mel, which have similar genomes (Gerth et al, 2020) but confer different levels of protection against wasps, measured as fecundity of flies surviving a wasp attack (Jones and Hurst, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments used the MSRO-Ug strain Spiroplasma strain originally collected from Namulonge, Uganda in 2005 (Pool et al ., 2006); this strain was transinfected onto a Canton-S background in 2020 (Jones and Hurst, 2020b). MSRO-Ug Canton-S stocks and Canton-S stocks lacking Spiroplasma were maintained on corn meal agar (10 g agarose, 85 g sugar, 60 g maize meal, 40 g autolysed yeast in a total volume of 1 L, to which 25 mL 10% Nipagin dissolved in 100% ethanol was added) at 25°C on a 12:12 light:dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Spiroplasma is a facultative symbiont of Drosophila and has been shown to protect against parasitoid wasps and nematodes (Xie et al ., 2010; Jaenike et al ., 2010), and the strain in D. melanogaster combines protection phenotype with male-killing. Previous studies on this system have concluded that the strain of wasp and Spiroplasma are all important components for the outcome of Spiroplasma -mediated protection (Jones and Hurst, 2020a; Jones and Hurst, 2020b). Whilst influence of temperature on the protective phenotype have not been established, vertical transmission of Spiroplasma in D. melanogaster fails at 16.5°C, indicating cool sensitivity of the symbiosis (Montenegro and Klaczko, 2004).…”
Section: Introductionmentioning
confidence: 99%